JUAL BELI BITCOIN DALAM PERSPEKTIF EKONOMI ISLAM - Moch Zaenal Azis Muctharom; Moh. Agus Sifa' (Journal of Islamic Banking, 2022)
Bitcoin is one of several digital currencies that first appeared in 2008 which was introduced by Satoshi Nakamoto as a currency based on cryptography. Bitcoin is a payment network based on peer-to-peer technology. Peer-to-peer network is a network that acts as a server as well as a client. Every Bitcoin transaction is stored in the database of the Bitcoin network. When a transaction occurs with Bitcoin, buyers and sellers will automatically be recorded in the Bitcoin database network. Bitcoin has advantages and disadvantages. The advantage of Bitcoin is that it is safe because every currency transaction is governed by a cryptography algorithm so that there is no possibility for counterfeiting currency balances. The drawback is that the Bitcoin system is anonymous, making Bitcoin vulnerable to cybercrime, if Bitcoin is lost, you cannot be insured because Bitcoin is not bound by any institution or law. Bitcoin as a means of payment transactions. This is because Bitcoin does not meet several elements and criteria as a valid currency, especially in the principles of Islamic Economics. In the context of digital money, there is no underlying, that is, assets are used as the basis for transactions. In this case, two things can be concluded. First, digital money is not currency. Second, there is an element of ambiguity (Gharar). n this case Bitcoin has no Underlying Assets, prices do not represent Underlying Assets, prices are out of control and the function of this digital currency has developed from being a medium of exchange to an investment commodity.